Foxo1 and Foxp1 play opposing roles in regulating the differentiation and antitumor activity of T(H)9 cells programmed by IL-7 - Bi, Enguang (Sci Signal, 2017)
Tumor-specific CD4(+) T helper 9 (T(H)9) cells, so-called because of their production of the cytokine interleukin-9 (IL-9), are a powerful effector T cell subset for cancer immunotherapy. We found that pretreatment of naïve CD4(+) T cells with IL-7 further enhanced their differentiation into T(H)9 cells and augmented their antitumor activity. IL-7 markedly increased the abundance of the histone acetyltransferase p300 by activating the STAT5 and PI3K-AKT-mTOR signaling pathways and promoting the acetylation of histones at the Il9 promoter. As a result, the transcriptional regulator Foxo1 was dephosphorylated and translocated to the nucleus, bound to the Il9 promoter, and induced the production of IL-9 protein. In contrast, Foxp1, which bound to the Il9 promoter in naïve CD4(+) T cells and inhibited Il9 expression, was outcompeted for binding to the Il9 promoter by Foxo1 and translocated to the cytoplasm. Furthermore, forced expression of Foxo1 or a deficiency in Foxp1 in CD4(+) T cells markedly increased the production of IL-9, whereas a deficiency in Foxo1 inhibited the ability of IL-7 to enhance the differentiation and antitumor activity of T(H)9 cells. Thus, we identified the roles of Foxo1 as a positive regulator and Foxp1 as a negative regulator of T(H)9 cell differentiation and antitumor activity, which may provide potential targets for cancer immunotherapy.